Community health workers’ quality of comprehensive care: a cross-sectional observational study across three districts in South Africa - Babalola, Olukemi; Levin, Jonathan; Goudge, Jane; Griffiths, Frances (Frontiers in Public Health, 2023)
Background: Community healthcare worker (CHWs) training programs are becoming increasingly comprehensive (an expanded range of diseases). However, the CHWs that the program relies on have limited training. Since the CHWs activities occur largely during household visits, which often go unsupervised and unassessed, long-term, on-going assessment is needed to identify gaps in CHW competency for further strengthening. We observed CHWs during household visits and gave scores according to what proportion of health messages/activities provided for the health conditions encountered in the households. We aimed to determine 1) messages/activities scores derived from the proportion of health messages given in the households by CHWs who provide comprehensive care in South Africa, and 2) the associated factors.In three districts (from two provinces), we trained five fieldworkers to score the messages provided by, and activities of, 34 CHWs that we randomly-selected, during 376 household visits in 2018 and 2020 using a cross-sectional study design. Multilevel models were fitted to identify factors associated with the messages/activities score, adjusted for the clustering of observations within CHWs. The models were adjusted for fieldworkers study facilities (n=5, respectively) as fixed effects. CHW-related (age, education level, and phase of CHW training attended/passed) and household-related factors (household size [number of persons per household], number of conditions per household, and number of persons with a condition (hypertension, diabetes, HIV, tuberculosis [TB], and cough) were investigated.In the final model, messages/activities score increased with each extra 5-minute increase in visit duration. Messages/activities scores were lower for households with either children/babies, This is a provisional file, not the final typeset article hypertension, diabetes, increasing household size, increasing number of household conditions and members with either TB or cough. The messages/activities scores were not associated with any CHW characteristics, including education and training.Conclusions: This study identified important factors related to the messages provided by, and activities of CHWs, across CHW teams. Increasing efforts are needed to ensure that CHWs who provide comprehensive care are supported given the wider range of conditions they provide messages/activities for, especially in households with hypertension, diabetes, TB/cough, and those with children and babies.